145k views
20 votes
Find the missing values in the equation below.

Line 1: 2/3 - 1/2 = 4/?-?/6
Line 2: / - / = ?/6

User AwongCM
by
4.6k points

1 Answer

11 votes

Answer:


(2)/(3) - (1)/(2) = (4)/(6) - (3)/(6)


(2)/(3) - (1)/(2) = (1)/(6)

Explanation:

Given


(2)/(3) - (1)/(2) = (4)/(?) - (?)/(6)


/ - / = (?)/(6)

Required

Fill in the gaps

For Line 1, convert both fraction to a denominator of 6.

This is shown below:


(2)/(3) - (1)/(2) = (4)/(?) - (?)/(6)


(2)/(2)*(2)/(3) - (1)/(2) *(3)/(3)


(2*2)/(2*3) - (1*3)/(2*3)


(4)/(6) - (3)/(6)

Hence:


(2)/(3) - (1)/(2) = (4)/(6) - (3)/(6)

For Line 2;

We have:


(2)/(3) - (1)/(2) = (4)/(6) - (3)/(6)


(2)/(3) - (1)/(2) = (4-3)/(6)


(2)/(3) - (1)/(2) = (1)/(6)

User Jmzagorski
by
5.3k points